ANALISIS IMPLEMENTASI ADMINISTRASI SEKOLAH - Ade Hermawan; Abd. Rohman (REFORMASI, 2021)
Abstract: Administrative order and regularity  required because it is one of the important components for learning process. Some school administrations are considered not good enough so that school administration and archives become piled up and it is difficult to retrieve them when needed. This study aimed to analyze the implementation of school administration tasks with evaluation method, which is a method that evaluated the success of implementing a program/activity. Data collection techniques used distributing questionnaires, observation, and documentation. Furthermore, the data were analyzed qualitatively. The results showed that the implementation of school administration in the areas of personnel administration, financial administration, infrastructure administration, public relations administration, archive administration, and student administration were in good category. Overall there are 67% of respondents who answered good administrative services, 31% answered quite well, and 2% answered less well. It can be concluded that the implementation of school administration work in general is good.Keywords: school administration; administration; service; data collectionAbstrak: Ketertiban dan keteraturan administrasi sangat diperlukan karena menjadi salah satu komponen penting dalam proses pembelajaran. Sebagian administrasi sekolah dinilai tidak cukup baik sehingga administrasi dan kearsipan sekolah menjadi bertumpuk dan sulitnya mengambil kembali saat dibutuhkan. Penelitian ini bertujuan menganalisis pelaksanaan tugas tata usaha sekolah dengan metode evaluasi, yakni metode yang digunakan untuk memberikan penilaian pada suatu kegiatan/program. Teknik pengumpulan data dilakukan dengan penyebaran kuesioner, observasi, dan dokumentasi. Selanjutnya data dianalisis secara kualitatif. Hasil penelitian menunjukkan pelaksanaan Administrasi Sekolah pada bidang administrasi kepegawaian, administrasi keuangan, administrasi sarana prasarana, administrasi hubungan masyarakat, administrasi kearsipan, dan administrasi kesiswaan berada pada kategori baik. Secara keseluruhan terdapat 67% responden yang menjawab pelayanan administrasi baik, 31% menjawab cukup baik, dan 2% menjawab kurang baik. Artinya dapat disimpulkan bahwa pelaksanaan pekerjaan administrasi sekolah secara umum sudah baik.  Kata kunci: administrasi sekolah; tata usaha; pelayanan; pendataan